Long Term Efficacy and Safety of Cardiac Resynchronization Therapy in Adult Congenital Heart Disease Patients: A Single Center Cohort Study - Schamroth Pravda, Nili; Richter, Ilan; Brem, Ofir; Yehuda, Daniel; Rahat, Ori; Ofek, Hadas; Tal, Shir; Kornowski, Ran; Vig, Shahar; Buturlin, Kirill; Hirsch, Rafael; Golovchiner, Gregory (The American journal of cardiology, 2025)
•This study provides real-world evidence showing CRT is effective in ACHD patients, regardless of ventricular morphology or baseline ejection fraction.•CRT is beneficial as both a therapeutic and preventative treatment. Heart failure constitutes a major cause for morbidity amongst patients with adult congenital heart disease (ACHD). Cardiac resynchronization therapy (CRT) is a recommended therapeutic measure for patients with heart failure. Data on the efficacy and safety of CRT amongst patients with ACHD is limited. This study analyzed data from a retrospective cohort of patients with ACHD and implantation of CRT between 2015 and 2022. The primary outcome was echocardiographic response to CRT, defined as either: (1) an increase in systemic ventricular ejection fraction (EF) of ≥ 5% in patients with baseline EF <50% (therapeutic efficacy) or (2) maintenance of EF in patients with EF ≥ 50% (preventative efficacy). The outcomes were assessed by subgroups of systemic left or right ventricle ventricle. In a cohort of 45 patients, mean age was 54 ± 14 years, 26 patients had a systemic left ventricle (57.8%) and 19 patients had a systemic right ventricle (42.2%). The average follow-up was 5.2 ± 0.5 years. Primary outcome amongst patients with reduced EF at baseline was achieved in 69.0%; and in 92.3% amongst patients with preserved EF at baseline. There was no significant difference in the response to CRT as per systemic left or right ventricle (p = 0.15) or per baseline EF (p = 0.10). Complications occurred in 28.9% of patients. In conclusion, CRT appears to be effective in patients with ACHD in reducing rates of heart failure, regardless of baseline EF or systemic ventricle morphology. The percentage of patients with a safety outcome was relatively high and highlights the need for careful patient selection.